Categorizing DLT researches and its applications - Shokripour, Amin; Othman, Mohamed (EuroJournals Publishing, 2009)
During the last decade, using parallel and distributed system has become general. In these systems, a huge size of data or computation is distributed among many systems to get better performance. Dividing data is one of the challenges in this type of systems. Divisible Load Theory (DLT) is one of the proposed methods for scheduling data distribution in parallel or distributed systems. Many researches have been done in this field and some applications have been introduced for it. A novice researcher in this field needs to know thing about DLT such as history, fundamental concepts, terminology, important parameters and DLT applications. In this article after history and terminology, previous researches have been categorized in some class based on investigated parameters in each of them. Then some of general applications of DLT are mentioned.